Natural Convection and Irreversibility Evaluation in a Cubic Cavity with Partial Opening in Both Top and Bottom Sides - Öztop, Hakan Fehmi; Almeshaal, Mohammed A.; Kolsi, Lioua; Rashidi, Mohammed Mehdi; Ali, Mohamed E. (Mdpi, 2019)
A numerical study on natural convection in a cubical cavity with partial top and bottom openings is performed in this paper. One of the vertical walls of the cavity has higher temperature than that of the opposite one; the remaining walls are insulated perfectly. Three-dimensional simulations of governing equations have been performed using a finite volume technique. The results are presented for different parameters such as opening length and Rayleigh number. It is observed that heat transfer rate and fluid flow can be controlled via opening ratio size and Rayleigh number.
Keywords: open cavity; natural convection; entropy; 3D flow